THE EFFECT OF USING FOUR-SQUARE WRITING METHOD ON STUDENTS’ WRITING ABILITY AND VOCABULARY MASTERY AT SMK NURUL FALAH PEKANBARU - FELCI TRIA SAUHANA (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2021)
This research aims to find out the students’ writing ability category, to find out the students’ vocabulary mastery category, to find out whether the using of Four-Square Writing method can give the significant effect on students’ writing ability in descriptive text and to find out what extent the using of Four-Square Writing method gives the significant effect on students’ vocabulary mastery. The study of this research is quasi-experimental research that pre – test and post test deign are used in this research. The sample of this research is the first year students at SMK Nurul Falah Pekanbaru. They are experimental class and control class. The data were collecting by using writing in descriptive text and vocabulary tests. Four-Square Writing method was used by this research. The result of this research shows that 1. There is significant effect on implementing treatment of Four-Square Writing method toward students’ writing ability for experimental group. The T-test result was 19,868, its df was 28, comparing number of significance. If probability >0.05 null hypothesis (H0) is rejected. If probability <0.05, alternative hypothesis (Ha) was accepted. Because the significance was 0.000 < 0.05, thus, Ha was accepted while Ho was rejected. 2. There is significant effect on implementing treatment of GRASP strategy toward students’ vocabulary mastery for experimental class. The t-test result was 12,231,, its was df 28, by comparing number of significance. Because the significance was 0.000 < 0.05, thus, Ha was accepted while Ho was rejected.